The Effect of Private Information and Monitoring on the Role of Accounting Quality in Investment Decisions* - BEATTY, ANNE; SCOTT LIAO, W.; WEBER, JOSEPH (Contemporary Accounting Research, 2010)
We investigate how private information and monitoring affect the role of accounting quality in reducing the investment-cash flow sensitivity. We argue that access to private information and direct restrictions on investments are likely to affect the extent to which accounting quality reduces financing constraints. Our results suggest that for financially constrained firms, banks' access to private information decreases the value of accounting quality. We further find that, for both financially constrained and unconstrained firms, covenants directly restricting capital expenditures also mitigate the importance of accounting quality. Our results suggest that when information asymmetry problems are likely to be the largest, accounting quality is most important. However, the importance of accounting quality is mitigated if outside capital suppliers have access to private information and is eliminated if they impose contractual restrictions on investment. We also provide evidence that banks' access to private information reduces the cash flow sensitivity of cash and mitigates the importance of accounting quality in reducing this sensitivity. This additional evidence suggests that our investment-cash flow sensitivity results are not driven by measurement error of the investment opportunity set.